Implementasi Metode Eurel untuk Penyelesaian Persamaan Diferensial pada Dinamika Populasi - Aprilia Cristina Sianturi; Bali Sahputri Br Tarigan; Tantory Yahya Purba; Valeri Agatha Br Sihombing (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This study aims to solve the population dynamics model using the Euler method, where the model is a nonlinear differential equation. The research methods used are literature study and simulation methods. In theory, the Euler Method is a numerical method that is often used in solving initial value problems. The Euler method is obtained by decomposing a function into a Taylor series up to two initial terms. This method has an accuracy of one.